Sustainable Assessment of Academic Buildings at Universiti Teknologi Petronas Campus - Firdaus, Ahmad ‘Adnin (Universiti Teknologi PETRONAS, 2018)
Recently, Malaysia government has launched The Green Building Mission as an indication of a promising effort to brings sustainability in production and delivery of the construction industry products. Since then, many initiatives have been launched to propel and facilitate efforts toward a more environmental conscious building and construction industry in the region. “Due to this, developers, owners, operators, insurers and the public at large are beginning to value and market the benefit of sustainable building.”